Вимірювання часу реакції людини - Журавель, І. В.; Сайківська, Л. Ф. (My University, 2021)
In this work, the means of measuring the human response were considered. Reflexometers of different types are given. The principle of operation of the reflexometer is given. The STM32 microcontroller was called a good example to use and some of its characteristics are considered.
Keywords: вимірювання часу; реакція; рефлексометр